Application Of Parental Communication Patterns In Developing Children’s Self-Discipline In Navy Families In Sugihwaras-Sidoarjo Village - Anggreani, Nova Yunita; Sucipto, Sucipto; Listyaningrum, Anggia (Proceedings Series of Educational Studies, 2024)
The family is the smallest unit in society with various important roles. Parents in a family act as facilitators to provide direction to children, so that children can choose interests that they like and these interests become a form of responsibility and discipline for children in managing their time. Direction from parents can be given through implementing communication patterns between parents and children. The application of communication patterns used by parents will of course always vary depending on the patterns chosen and adapted to the conditions, development and problems being faced by the child. Just like what happens in Navy families. The aim of the research is to explain the application of parent-child communication patterns in Navy families in terms of developing children’s self-defense training discipline. This research uses qualitative research with a narrative descriptive approach. This research was located in Sugihwaras Village, Sidoarjo Regency. The research subjects selected based on predetermined criteria included the male parent (father), martial arts trainer, the child concerned and also their peers. In this research, the data collection techniques used were interviews, observation and documentation with data analysis in the form of data reduction, data presentation and also drawing conclusions. This research also uses two types of triangulation, namely, time triangulation and technical triangulation in order to obtain more valid research data. The result of this research is that with support or stimulus from parents in the form of implementing communication patterns that are combined in a balanced way when the communication process in the family takes place, children can develop time discipline within themselves. Implementing communication patterns provided by parents indirectly increases time discipline indicators in children. For this reason, the role of parents as facilitators for children in the family environment requires parents to support children in developing character values that are considered to bring positive and useful changes to children in the future. With the role of parents as facilitators for children, parents should be able to know the child's condition, problems and development so that later parents will be able to implement communication patterns that are appropriate to the child's condition and provide good results for the child's development. Keywords: Communication Patterns, Parents, Martial Discipline